Generating key practice points that enable optimal palliative care in acute hospitals: Results from the OPAL project's mid-point meta-inference - Claudia Virdun; Tim Luckett; Patricia M Davidson; Karl Lorenz; Jane Phillips (Elsevier, 2021)
Background: Internationally, the epidemiology of dying is changing with people dying at an older age from an expected death and with complex health care needs. An increasing proportion of people require hospital care with the need to strengthen the quality of this care well-articulated. Evidence about what enables optimal inpatient palliative care is available. Articulating how to enable this within clinical practice is required. Objective: To investigate the domains of care that are most important to inpatients with palliative care needs and their families, to generate key practice points to inform optimal clinical care provision. Design: A mid-point meta-inference of the Opal Project's data. The three phase Opal Project utilised a fully mixed sequential dominant design (Quan → QUAL). Phase 1 focused on 'scoping the problem' through a systematic review and meta-synthesis of important aspects of care for inpatients with palliative care needs and their families (studies 1a and 1b); Phase 2 focused on 'understanding importance' through a qualitative interview study (study 2); and a mid-point meta-inference of data obtained across Studies 1a, 1b and 2. Phase 3 included a global environmental scan (Study 3) and co-design workshop (Study 4) focused on understanding how to drive reform for Australian inpatient palliative care, based on outcomes from the mid-point meta-inference; and an end-point meta-inference to generate final recommendations. Methods: Mid-point meta-inference of data obtained across Phases 1 and 2 involving: 1) verifying synthesis of data with palliative care consumers and clinical leaders; and 2) populating joint display tables to inform analysis and generate practice points. Results: Three categories and 14 domains informing optimal inpatient palliative care were identified: 1) Person-centred care including respectful and compassionate care; effective communication and shared decision making; effective teamwork; enabling family involvement; and maintaining role, meaning and identity; 2) Expert care including excellence in physical care; impeccable assessment and care planning; effective symptom management; technical competence; patient safety; and supported access to senior clinicians; and 3) Optimal environment for care including patient and family focused structural factors; and cleanliness to support infection control. Data integration generated 68 practice points informing care provision. Conclusions: Through a synthesis of patient and family perspectives about what is important for optimal inpatient palliative care, this study confirmed three categories of care, 14 domains of importance and 68 practice points. Importantly, these practice points guide clinical practice to enable each domain of care in practice. Tweetable abstract: We know what patients with palliative care needs, and their families need for good care when they are in hospital. It is time to deliver care in line with these needs.